Smad7 Deficiency in Myeloid Cells Does Not Affect Liver Injury, Inflammation or Fibrosis after Chronic CCl4 Exposure in Mice - Ludmilla Unrau (MDPI AG, 2021)
Myeloid cells play an essential role in the maintenance of liver homeostasis, as well as the initiation and termination of innate and adaptive immune responses. In chronic hepatic inflammation, the production of transforming growth factor beta (TGF-β) is pivotal for scarring and fibrosis induction and progression. TGF-β signalling is tightly regulated via the Smad protein family. Smad7 acts as an inhibitor of the TGF-β-signalling pathway, rendering cells that express high levels of it resistant to TGF-β-dependent signal transduction. In hepatocytes, the absence of Smad7 promotes liver fibrosis. Here, we examine whether Smad7 expression in myeloid cells affects the extent of liver inflammation, injury and fibrosis induction during chronic liver inflammation. Using the well-established model of chronic carbon tetrachloride (CCl4)-mediated liver injury, we investigated the role of Smad7 in myeloid cells in LysM-Cre Smadfl/fl mice that harbour a myeloid-specific knock-down of Smad7. We found that the chronic application of CCl4 induces severe liver injury, with elevated serum alanine transaminase (ALT)/aspartate transaminase (AST) levels, centrilobular and periportal necrosis and immune-cell infiltration. However, the myeloid-specific knock-down of Smad7 did not influence these and other parameters in the CCl4-treated animals. In summary, our results suggest that, during long-term application of CCl4, Smad7 expression in myeloid cells and its potential effects on the TGF-β-signalling pathway are dispensable for regulating the extent of chronic liver injury and inflammation.